2010
DOI: 10.1161/circulationaha.110.954628
|View full text |Cite
|
Sign up to set email alerts
|

MG53 Constitutes a Primary Determinant of Cardiac Ischemic Preconditioning

Abstract: Background-Ischemic heart disease is the greatest cause of death in Western countries. The deleterious effects of cardiac ischemia are ameliorated by ischemic preconditioning (IPC), in which transient ischemia protects against subsequent severe ischemia/reperfusion injury. IPC activates multiple signaling pathways, including the reperfusion injury salvage kinase pathway (mainly PI3K-Akt-glycogen synthase kinase-3␤ [GSK3␤] and ERK1/2) and the survivor activating factor enhancement pathway involving activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
193
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 178 publications
(216 citation statements)
references
References 59 publications
15
193
5
1
Order By: Relevance
“…7C) were predominantly distributed in heavy fractions in perfusion hearts, and their phosphorylation level was significantly increased in IPC hearts. In addition, IPC also greatly increased caveolae-associated p-AKT, but not p-GSK-3␤, which was consistent with other findings, i.e., caveolaeenriched p-ERK1/2 and p-AKT upon stress exposure (5,53). Interestingly, IPC-induced changes and redistribution of these cellular signals were blocked by NPS2143 treatment, suggesting activation of CaSR is necessary for activating cardioprotective signaling.…”
Section: Signaling Pathways Involved In Cardioprotection Bysupporting
confidence: 91%
“…7C) were predominantly distributed in heavy fractions in perfusion hearts, and their phosphorylation level was significantly increased in IPC hearts. In addition, IPC also greatly increased caveolae-associated p-AKT, but not p-GSK-3␤, which was consistent with other findings, i.e., caveolaeenriched p-ERK1/2 and p-AKT upon stress exposure (5,53). Interestingly, IPC-induced changes and redistribution of these cellular signals were blocked by NPS2143 treatment, suggesting activation of CaSR is necessary for activating cardioprotective signaling.…”
Section: Signaling Pathways Involved In Cardioprotection Bysupporting
confidence: 91%
“…PI3K activity was determined using the PI3K Activity ELISA kit, according to the manufacturer's instructions (20,21). For BKM120 treatment, cells were treated with BKM120 (50 µM) for 48 h. For direct functional assessment of PI3K activity, PI3K was isolated by immunoprecipitation using an anti-PI3K antibody (cat.…”
Section: Methodsmentioning
confidence: 99%
“…They are subject to tight control at multiple levels, including differential localization, post-translational modification and the regulation of protein levels. SPRY participates in multiple physiological and pathological processes, including acute membrane repair, myogenesis in skeletal muscle and cardiac ischemic preconditioning (12,(15)(16)(17). Thum et al identified that SPRY1 was a direct target of miRNA-21 and mediated the effect of miRNA-21 in cardiac fibroblasts (18).…”
Section: Introductionmentioning
confidence: 99%